Transtornos mentais e o uso de agrotóxicos em município do oeste do Paraná: um estudo transversal - Coneglian, Ariady Lucia De Andrade (2020)
The use of pesticides and their effect on human health has been a relevant topic in current scientific research. It is known that all of them are potentially dangerous and can cause damage to the health of people, animals and the environment. Studies have shown associations between exposure to pesticides and the occurrence of mental disorders. Thus, this study aims to identify the occurrence of mental disorders in the rural population exposed to pesticides in the city of Ubiratã - PR. This is a descriptive, quantitative and qualitative study, with a cross-sectional design, and the data collection took place between November 2018 and July 2019 through the application of the modified Family Record of the Protocol for the Evaluation of Chronic Intoxications by Agrochemicals of Paraná to 235 families residing in that County. A semi-structured interview was also conducted with 11 family members of individuals who reported suffering from a mental disorder and whose diagnoses were confirmed in the search on electronic medical records. The data were analyzed using the k-proportions and adherence chi-square tests. The study sample was predominantly female (50.57%), aged up to 20 years (26.9%) followed by 51 to 60 years old (18.71%), agricultural occupation (24.29%) and with Incomplete Elementary School (46.44%), who carried out activities without the use of PPE (58.92%), with 13.58% of the participants having a mental disorder. Among the individuals surveyed, there was a positive association of mental disorders with the following variables: female gender; unemployed and retired; non-use of PPE; work on cotton and bean crops and laundry, harvesting and loading and unloading activities; having suffered previous acute poisoning, especially more than 10 times; and with the pesticides Glyphosate, Monocrotofós, Paration and Profenofós with Cypermethrin. The interviews revealed that the subjects dedicated themselves to agricultural activities for prolonged periods, did not use PPE and do not realize that the use of pesticides can trigger the development of mental disorders. This study showed that exposure to pesticides, whether directly or indirectly, can contribute to individuals' mental illness. It is aimed, through the presentation of these data, to strengthen and encourage the implementation of public policies for the care of rural populations exposed to pesticides. Finally, these data become useful to reinforce the findings of other studies that show the harmful effects of pesticide abuse and its association with mental disorders.